Answer:
add all of them and divide by 2
Step-by-step explanation:
Hello!
![\large\boxed{x^{4}}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7Bx%5E%7B4%7D%7D)
Recall that:
is equal to
. Therefore:
![\sqrt[3]{x^{2} } = x^{\frac{2}{3} }](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7Bx%5E%7B2%7D%20%7D%20%3D%20x%5E%7B%5Cfrac%7B2%7D%7B3%7D%20%7D)
There is also an exponent of '6' outside. According to exponential properties, when an exponent is within an exponent, you multiply them together. Therefore:
![(x^{\frac{2}{3} })^{6} = x^{\frac{2}{3}* 6 } = x^{\frac{12}{3} } = x^{4}](https://tex.z-dn.net/?f=%28x%5E%7B%5Cfrac%7B2%7D%7B3%7D%20%7D%29%5E%7B6%7D%20%20%3D%20x%5E%7B%5Cfrac%7B2%7D%7B3%7D%2A%206%20%7D%20%20%3D%20x%5E%7B%5Cfrac%7B12%7D%7B3%7D%20%7D%20%3D%20x%5E%7B4%7D)
11/12* (1/6)
= 11/72.
The final answer is 11/72~
Answer: a
Step-by-step explanation:
![\left(\frac{f}{g} \right)(x)=\frac{f(x)}{g(x)}=\frac{\sqrt{x^{2}-1}}{\sqrt{x-1}}}=\sqrt{\frac{x^{2}-1}{x-1}}=\sqrt{\frac{(x-1)(x+1)}{x-1}}=\boxed{\sqrt{x+1}}](https://tex.z-dn.net/?f=%5Cleft%28%5Cfrac%7Bf%7D%7Bg%7D%20%5Cright%29%28x%29%3D%5Cfrac%7Bf%28x%29%7D%7Bg%28x%29%7D%3D%5Cfrac%7B%5Csqrt%7Bx%5E%7B2%7D-1%7D%7D%7B%5Csqrt%7Bx-1%7D%7D%7D%3D%5Csqrt%7B%5Cfrac%7Bx%5E%7B2%7D-1%7D%7Bx-1%7D%7D%3D%5Csqrt%7B%5Cfrac%7B%28x-1%29%28x%2B1%29%7D%7Bx-1%7D%7D%3D%5Cboxed%7B%5Csqrt%7Bx%2B1%7D%7D)
Answer:
B. 13 units
Step-by-step explanation:
let
(x1 , y1) = (-4 , -6)
(x2 , y2) = (1 , 6)
distance between CD = root (x2 - x1)^3 + (y2 - y1)
= root {1 - ( -4)}^2 + {6 - ( -6)}^2
= root {1 +4}^2 + {6+6}^2
= root 5^2 + 12^2
= root 25 + 144
= root 169
= 13 units ans